La Gestión de la Unidad de Desarrollo Humano del GAD Provincial de Cotopaxi y su incidencia en el desarrollo sostenible. - Pincha Anguisaca, María Ofelia (2023)
The public administration constitutes a service to the community, under the principles of effectiveness, efficiency, speed, among others, which together seek to deliver a quality service to the citizen. The management of this administration is aligned with the National Development Plan, which seeks to meet the Sustainable Development objectives set for the 2030 agenda. Sustainable development includes the ability of an administration to cover the basic needs of citizens , without compromising the future, within the economic and environmental field. This research focuses its study on the management of the Rights and Interculturality Unit, belonging to the Directorate of Productive Promotion and Human Development, of the Provincial Decentralized Autonomous Government of Cotopaxi and its impact on Sustainable Development.